The Predictive Role of Preoperative Leukocytosis, Anemia and Thrombocytosis with the Severity of Epithelial Ovarian Tumors - Sh Yazdani; M Javadian; Z Bouzari; M Ranaei; K Hajian; A Ghafari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2018)
BACKGROUND AND OBJECTIVE: Ovarian cancer is the sixth common cancer among women in the world. Preoperative blood cell count can be a biomarker that predicts the severity of different types of cancer and determine the type of surgery. Therefore, the present study was conducted to determine the predictive role of the three blood markers of anemia, leukocytosis and thrombocytosis in the stage and grade of epithelial ovarian cancer before the operation. METHODS: In this cross-sectional study, the data of 60 patients with epithelial ovarian cancer were evaluated. Demographic data, hemoglobin, white blood cell count and platelets were statistically compared based on the stage of disease and the grade of mass differentiation as good, moderate and undifferentiated. FINDINGS: 61.1% of patients with thrombocytosis were in stage 3 and 33.3% of patients with leukocytosis were in stage 2 (p≤0.05), while 20.5% of the patients with anemia were in stage 3 (p>0.05). Moreover, 52.4% of patients with leukocytosis and 61.1% of patients with thrombocytosis had grade 3 tumor (p≤0.05), but only 34.1% of patients with anemia were in this group (p>0.05). Based on the evaluation of the ROC curve, cut-off point of the white blood cell was calculated to be 9050/ml with a sensitivity of 64% and specificity of 65% and platelet count was calculated to be 266000/ml with a sensitivity of 88% and specificity of 53%. CONCLUSION: Based on the results of this study, preoperative leukocytosis and thrombocytosis were correlated with stage and grade of epithelial ovarian cancer and had a predictive role.